Performance Analysis of Routing Protocols in Ad-Hoc Networks: A Comparative Study of AODV, DSR, and OLSR - Dimantara, William; Yusnanto, Tri; Arsan, Wansen Rey; Ginting, Suheri (Journal Basic Science and Technology, 2024)
This research investigates the performance of three prominent routing protocols Ad-hoc On-Demand Distance Vector (AODV), Dynamic Source Routing (DSR), and Optimized Link State Routing (OLSR) in ad-hoc networks. Through comprehensive simulations, we evaluate key performance metrics including Packet Delivery Ratio (PDR), End-to-End Delay, Routing Overhead, and Throughput across varying network densities and mobility conditions. The results demonstrate that AODV consistently outperforms DSR and OLSR, particularly in high-density and dynamic environments, achieving higher PDR and lower delays. DSR exhibits competitive performance under moderate conditions but struggles in dense scenarios due to increased overhead and route instability. OLSR, while effective in static networks, shows significant limitations in mobile environments, resulting in higher routing overhead and delays. The findings emphasize the importance of selecting appropriate routing protocols based on specific application requirements and network conditions. This research contributes to the existing literature by providing insights into the relative performance of these protocols, highlighting the need for ongoing exploration of adaptive and hybrid solutions to address the challenges faced in real-world applications of ad-hoc networks.